Pollution Water Quality Of Any Potential Acid Mine Drainage The Result Coal Mining (Study Case In Patangkep River) - Kaharapenni, Marlina; Noor, Rudy Hendrawan (INTEKNA informasi teknik dan niaga, 2015)
At level pollution in location research the caused of any contamination between the bedrock exposed with air, and water (either water from in location mining although rain water). Metal heavy with be found in accumulation overburden although coal, oxidize with minerals a sulphide of so raises the potential acid mine drainage, the condition talked opportunity occurred pollution water quality. This occurs on Patangkep river, the where content of unsure acided and metal heavy on contained in water. As there is any unsure minerals sulphide that is sulfat acid (SO4); 390,61 mg/l, unsure metal heavy as iron (Fe); 3,10 mg/l, and manganase (Mn); 3,815 mg/l. Than presention value obtained, weather level limits of parameters of coursed. While on the bedrock and layer rock as carbon mudstone, mudstone at parting and roof, as well clay stone raises of any is potential acidity. Be based on result research indicated that status grade water Patangkep river be at class C â€œsoiled mediumâ€ this occurs finded be based on parameter chemical (pH and metal heavy).